2018
DOI: 10.1111/bjd.16540
|View full text |Cite
|
Sign up to set email alerts
|

Demodex mites modulate sebocyte immune reaction: possible role in the pathogenesis of rosacea

Abstract: Demodex mites have the capacity to modulate the TLR signalling pathway of an immortalized human sebocyte line. Mites have the capacity to secrete bioactive molecules that affect the immune reactivity of sebocytes. Increasing mite numbers influenced interleukin-8 secretion by these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
96
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 54 publications
4
96
1
2
Order By: Relevance
“…1,2 Although still controversial, [3][4][5] evidence supporting a role of Demodex in papulopustular rosacea (PPR) is accumulating, [6][7][8][9][10] and recent guidelines for the treatment of rosacea include use of ivermectin, an acaricidal drug, as a first-line topical treatment for PPR. 1,2 Although still controversial, [3][4][5] evidence supporting a role of Demodex in papulopustular rosacea (PPR) is accumulating, [6][7][8][9][10] and recent guidelines for the treatment of rosacea include use of ivermectin, an acaricidal drug, as a first-line topical treatment for PPR.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although still controversial, [3][4][5] evidence supporting a role of Demodex in papulopustular rosacea (PPR) is accumulating, [6][7][8][9][10] and recent guidelines for the treatment of rosacea include use of ivermectin, an acaricidal drug, as a first-line topical treatment for PPR. 1,2 Although still controversial, [3][4][5] evidence supporting a role of Demodex in papulopustular rosacea (PPR) is accumulating, [6][7][8][9][10] and recent guidelines for the treatment of rosacea include use of ivermectin, an acaricidal drug, as a first-line topical treatment for PPR.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, Demodex infestation was associated with enhanced total blood and skin‐homing T reg cell levels. Accordingly, agents secreted by mites were previously reported to exert immune‐modulating activities and help to avoid induction of host inflammatory mediators . TGF‐β and IL‐10, which are cytokines associated with T reg differentiation and function, were also implicated in canine demodicosis .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the inflammatory eruption of Demodex folliculitis is a result of immune reconstitution in post‐HCT patients or those with HIV on antiretroviral therapy . Studies have demonstrated that the mite can stimulate the immune system, resulting in an inflammatory response, which patients are prone to once their immune system is restored . Treatment for Demodex ‐associated dermatitis can be achieved with topical sulfur, permethrin, or ivermectin (either oral or topical) .…”
Section: Discussionmentioning
confidence: 99%